Самораспространяющийся высокотемпературный синтез керамических матриц на основе обогащенного цирконием пирохлора для иммобилизации актинидсодержащих отходов - Подболотов, К. Б. (БНТУ, 2014)
The paper presents the results of the study on self-propagating high-temperature synthesis of mineral matrices based on phase of pyrochlore (Y2Ti2O7) and zirconia additives for immobilize actinide-containing waste (HLW). Investigations carried out in the system Ti - ZrO2 - CaO - Y2O3 - MenOm (Me = Mo, Fe, Ni, Cr, Mn, Cu) using models HLW. But such oxides as MoO3, CuO, MnO2 and metals reduced from them at high temperatures are exposed to increased ash due to evaporation. There under the perspective is the use of Fe2O3 as an oxidant. It is found that the components of HLW do not form an individual crystalline phases and includes as isomorphic impurities in the crystal lattice of pyrochlore, zirconolite and perovskite. A matrix material consisting of two phases – enriched by zirconium pyrochlore, containing HLW elements and metallic iron is produced. Substitution of titanium atoms to zirconium in the pyrochlore lattice is made up to 26 at. %.